Effect of Insulin on the Secretion and Content of Triglyceride in the Chicken Liver Slices - Shahriari, Ali; Pourkabir, Mlaihe; Asadi, Farzad; Atyabi, Nahid; Modirsanei, Mehrdad (International Journal of Poultry Science, 2005)
Triglyceride (TG) secretion from liver and its storage in abdominal cavity of the broiler affects the net meat yield. So agents that affect the hepatic TG secretion may be important for poultry breeders. At present study, we have shown short term effects of insulin on the chicken liver TG secretion at the first, third, fifth and seventh weeks of breeding. For this purpose, 10-10, 10-8 and 10-6 M insulin were added to the liver slices of roosters and TG secretion and content followed after 4h and 8h incubation. Results showed, while 4h incubation had no effect on TG secretion from the liver slices at the first, third and fifth weeks, in the seventh week 10-10 and 10-8 M insulin drastically decreased TG secretion 32% and 35% below the basal levels and 10-6 M insulin increased it 31% above the basal levels. In 8h incubation, while 10-6 M insulin at the first, third and fifth weeks decreased TG secretion below the basal levels (58%, 54%, and 39%), it showed 29%, 121%, and 128% increase in the seventh week when compared to the basal level, 10-10 and 10-8M insulin, respectively. At the first and seventh weeks TG content did not show response to insulin but in the third and fifth weeks showed a dose dependent increase. Insulin mainly decreases TG secretion from the chicken liver yet increases TG content as an age dependent manner.